Getting the balance right: Scaling-up treatment and prevention. Issue 4 (3rd April 2017) - Hoos, David; El-Sadr, Wafaa M; Dehne, Karl-Lorenz
ABSTRACT: The goals of the international response to control the HIV epidemic include high antiretroviral therapy (ART) coverage with HIV viral suppression, as well as reduction of new infections. ART use at individual and population levels reduces HIV morbidity and mortality and likely reduces HIV incidence. HIV viral suppression requires high levels of ART adherence, which necessitates support through behavioural and structural interventions to optimise effectiveness of the use of ART for prevention. Many people living with HIV remain unaware that they are HIV-infected, and HIV transmission risk is high during early infection, therefore ART expansion should be accompanied by other interventions in order to achieve the promise of treatment for prevention. Biomedical and behavioural prevention efforts focused on HIV-uninfected individuals at substantial risk of HIV acquisition are also needed to control the epidemic. Maintaining prevention programming is essential during the scale up of ART to reduce HIV transmission.